Foot Problems and Their Associations with Toe Grip Strength and Walking Speed in Community-Dwelling Older Individuals Using Day Services: A Cross-Sectional Study - Kashiko Fujii; Atsuko Maekawa; Takuyuki Komoda; Nozomi Kawabe; Ryouhei Nishimura; Yasunori Sakakibara; Takahiko Fukumoto; Minna Stolt (Nursing Reports, 2023)
Foot disorders in older individuals compromise balance and contribute to postural and gait instabilities, causing a decrease in the activities of daily living and quality of life. In this cross-sectional study, we analyzed the foot-related data of 160 frail older participants who attended day service centers in A prefecture in Japan to determine the prevalence of foot problems and their associations with toe grip strength and walking speed in frail older people. Multiple regression analysis was used to identify foot-related variables that correlated with toe grip strength and walking speed. The prevalence rates of skin dryness (Support level 88.2%, Care level 85.2% for men; Support level 84.9%, Care level 93% for women) and suspected and existing fungal infections in nails (Support level 94.1%, Care level 92.6% for men; Support level 98.1%, Care level 95.2% for women) were high in both sexes regardless of the level of care required. Furthermore, in both sexes, the prevalence rates of toe and arch deformities were significantly increased in the people who required care. Regression analysis revealed that some right-sided foot-related problems were significantly associated with right toe grip strength and walking speed. The decrease in toe grip strength was significantly associated with walking speed. Our study provides evidence that some specific conditions were associated with toe grip force and walking speed. This finding can contribute to future strategies to protect foot health in community-dwelling older individuals.